2012
DOI: 10.2118/146087-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Polymer Flooding With In-Depth Profile Modification

Abstract: For stratified reservoirs with free crossflow and where fractures do not cause severe channeling, improved sweep is often needed after water breakthrough. For moderately viscous oils, polymer flooding is an option for this type of reservoir. However, in recent years, an in-depth profile-modification method has been commercialized in which a block is placed in the high-permeability zone(s). This sophisticated idea requires that (1) the blocking agent have a low viscosity (ideally a unit-mobility displacement) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…In addition to that, porosity reduction and the change in the dispersion coefficient were obtained by the injection of a tracer into the core (before and after XL polymer injection). Tracer transport in porous media was modelled by fitting an experimental breakthrough curve for a tracer with a one-dimensional advection-dispersion model, where porosity and dispersion are matching parameters (Sorbie 1991;van der Hoek et al 2001;Seetha et al 2014). The two tracer tests show a porosity reduction of 6% and an increase in the dispersion coefficient by a factor of 20 which indicates that the in situ cross-linking took place in the porous media.…”
Section: Polmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to that, porosity reduction and the change in the dispersion coefficient were obtained by the injection of a tracer into the core (before and after XL polymer injection). Tracer transport in porous media was modelled by fitting an experimental breakthrough curve for a tracer with a one-dimensional advection-dispersion model, where porosity and dispersion are matching parameters (Sorbie 1991;van der Hoek et al 2001;Seetha et al 2014). The two tracer tests show a porosity reduction of 6% and an increase in the dispersion coefficient by a factor of 20 which indicates that the in situ cross-linking took place in the porous media.…”
Section: Polmentioning
confidence: 99%
“…In-depth profile modification is a promising technology for improving the sweep efficiency of water flooded heterogeneous oil reservoirs (Seright et al 2011;Sydansk and Southwell 2000;Bailey et al 2000;Glasbergen et al 2014). It can be implemented by injecting a crosslinking polymer (XL polymer) that propagates deep into the reservoir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proponents believe that microgels will primarily invade these high permeability zones as long as the microgel solution/gelant is of low viscosity; it is thought that the microgel solutions would essentially act as water does during injection. This, as well as steric effects, would minimize their penetration into other less permeable zones (Cozic et al, 2009;Seright et al, 2011). Another possible reason for minimal microgel penetration of low permeability layers is the relatively large microgel size (Zaitoun et al, 2007).…”
Section: Possible Conformance Control Mechanismsmentioning
confidence: 99%
“…5,6 The water-plugging performance of polymer gel systems in heterogeneous reservoirs is satisfactory, but it is unfavorable when they are used in fractured reservoirs. Seright and coworkers [6][7][8][9] have investigated the plugging performance of polymer/Cr 31 gels in fractures for many years. They found that the diffusion loss of chromium from gelant to brine could greatly reduce the gel strength or even make the gelant ungelled, and finally, it resulted in plugging ineffectiveness.…”
Section: Introductionmentioning
confidence: 99%